HIGHER ORDER THINKING SKILLS DALAM KOMPETENSI DASAR BAHASA ARAB - Muradi, Ahmad; Mubarak, Faisal; Darmawaty, Ridha; Hakim, Arif Rahman (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2020)
Learning Arabic is more dominant as a skill than a Science. The learners’ goals are able to use Arabic both spoken and written well and correctly. While HOTS is more dominant in requiring learners to think integrally. Therefore, it is important to consider the extent to which the Ministerial Regulation accommodates HOTS through a study of the basic competence of Arabic contained in it. This study is a literature review of the basic competence of Arabic in the Decree of the Minister of Religion (KMA) number 183 in 2019 in HOTS perspective. The object of this study is the basic competence of Arabic in KMA 183 in 2019. The result shows the basic competence of Arabic in KMA 183 in 2019 to accommodate the ability in higher order thinking such as problem solving, critical thinking, and reasoning. While the Basic Competence in KMA didn’t achieve creative thinking and decision making.